The potential use of natural vs commercial biosorbent material to remediate stream waters by removing heavy metal contaminants. (1st February 2019) - Richards, Samia; Dawson, Julian; Stutter, Marc
Abstract: The presence of high level of heavy metals in aquatic environment is a cause of ecological and environmental concern and thus their removal from water courses is environmentally essential. Four natural inexpensive biosorbents: macro algae ( Fucus vesiculosus ), crab shells ( Cancer pagurus ), wood chippings and iron-rich soil were tested for copper (Cu 2+ ) and zinc (Zn 2+ ) removal from aqueous solutions. Batch equilibrations were performed at 1:100 w/v with different initial metal concentrations. Three macro algae pre-treatments (unmodified (UM algae), chemically treated (Ca-T algae) and thermally treated (T-T algae)) were additionally investigated for performance. The sorption capacities were compared with the commercial material biochar and activated carbon. The maximum level of the sorbents for Cu 2+ uptake at 15.7 mM/l was attained by the natural material of UM algae (72.37 ± 0.37 mg/g) > Ca-T algae (66.77 ± 0.19 mg/g) > T-T algae (63.06 ± 0.82 mg/g), followed by the commercial material activated carbon (36.71 ± 2.20 mg/g). The maximum level of the sorbents for Zn 2+ uptake at 15.3 mM/l was also achieved by the natural material of UM algae (52.40 ± 0.80 mg/g) > Ca-T algae (48.83 ± 2.01 mg/g) > T-T algae (39.57 ± 0.80 mg/g) followed by the commercial material activated carbon (20.78 ± 1.63 mg/g) and biochar (18.07 ± 1.09 mg/g). The results demonstrated that Cu 2+ and Zn 2+ were effectively removed by these biosorbents at all concentrations. However, at high metals concentrations, the natural material macro algae had greater Cu 2+ and Zn 2+ sorption capacity than the conventional sorbent activated carbon, and the affinity of these natural biosorbents were greater for Cu 2+ than Zn 2+ . Hence, inexpensive natural and readily available materials showed potential as biosorbents to remediate polluted stream water of toxic metal contaminants. Highlights: Natural material exhibited high capability of metals removal from aqueous solutions. Modification of macro algae did not enhance its adsorption performance. H + ions competed with Cu 2+ and Zn 2+ ions for sorbents' surface binding sites. Crab shells exhibited greater affinity to Zn 2+ than Cu 2+ at low metal concentrations. Activated carbon's performance was reduced at high metal concentration and low pH.